Transcriptomically Revealed Oligo-Fucoidan Enhances the Immune System and Protects Hepatocytes via the ASGPR/STAT3/HNF4A Axis - Cheng, Chun-Chia (Biomolecules, 2020)
Oligo-fucoidan, a sulfated polysaccharide extracted from brown seaweed, exhibits anti-inflammatory and anti-tumor effects. However, the knowledge concerning the detailed mechanism of oligo-fucoidan on liver cells is obscure. In this study, we investigate the effect of oligo-fucoidan in normal hepatocytes by transcriptomic analysis. Using an oligo-fucoidan oral gavage in wild-type adult zebrafish, we find that oligo-fucoidan pretreatment enhances the immune system and anti-viral genes in hepatocytes. Oligo-fucoidan pretreatment also decreases the expression of lipogenic enzymes and liver fibrosis genes. Using pathway analysis, we identify hepatocyte nuclear factor 4 alpha (HNF4A) to be the potential driver gene. We further investigate whether hepatocyte nuclear factor 4 alpha (HNF4A) could be induced by oligo-fucoidan and the underlying mechanism. Therefore, a normal hepatocyte clone 9 cell as an in vitro model was used. We demonstrate that oligo-fucoidan increases cell viability, Cyp3a4 activity, and Hnf4a expression in clone 9 cells. We further demonstrate that oligo-fucoidan might bind to asialoglycoprotein receptors (ASGPR) in normal hepatocytes through both in vitro and in vivo competition assays. This binding, consequently activating the signal transducer and activator of transcription 3 (STAT3), increases the expression of the P1 isoform of HNF4A. According to our data, we suggest that oligo-fucoidan not only enhances the gene expression associated with anti-viral ability and immunity, but also increases P1-HNF4A levels through ASGPR/STAT3 axis, resulting in protecting hepatocytes.